Knowledge and Preventive Practices on Dengue Fever among Community People in Janakpurdham, Nepal - Pandey, Smita; Yadav, Punita; Mahato , Srijana; Dahal , Laxmi (Journal of Biratnagar Nursing Campus, 2025)
Background: Dengue is a viral infection transmitted to humans through the bite of infected mosquitoes and is found in tropical and sub-tropical climates worldwide, mostly in urban and semi-urban areas. According to the Epidemiology and Disease Control Division (EDCD) of the Ministry of Health and Population, Dengue is endemic in Nepal. Dengue is caused by a virus that is mostly transmitted by the bite of female mosquitoes of the species Aedes aegypti. This study aims to assess the knowledge and preventive practices regarding dengue fever among community people in Jankpurdham. Methodology: A Descriptive cross-sectional research design was conducted in ward no 14 of Janakpurdham sub-metropolitan city of Dhanusha, and samples were selected using the purposive sampling method. A total of 156 samples with an age range of 18 to 60 years were interviewed using the structured questionnaire. Data was analyzed using SPSS version 11.5. Descriptive statistics were used to describe socio-demographic data. The chi-square test was used to find out the association between dependent and independent variables. Results: According to findings of the study, the Mean ± SD of age was (39±10.99). Around 55.1% (86) were male, and 44.9% (70) were female. Thus, giving a male-to-female ratio of 7:6. Nearly half of the subjects (41.73%) were illiterate. Regarding occupational status, most of the respondents were found. The majority of the respondents (78.8%) had poor knowledge regarding dengue fever. This study reveals that good practice was found to be (51.5%) and poor practice (40.8%). The mean and standard deviation for the level of practice were 1.4423 and 0.49, respectively. Conclusion: The respondents’ knowledge regarding dengue fever was poor. There was no significant association between the level of knowledge and age, gender, family income, or occupational status of the respondents. Religion, which is more significant with the level of knowledge, is seen as a deficit in preventive practices of dengue fever. More than half of the respondents had good preventive practices against dengue fever.